112k views
3 votes
Rearrange the formula:
C = (F - 32)
to make F the subject
help

User Tguclu
by
6.0k points

2 Answers

1 vote
C = (F - 32)

C = F - 32 (remove the bracket)

- F = - 32 - C (change the subject to F)

F = 32 + C (remove the negative sign from the subject & change the sign to everything at the right hand side)

Final answer , F = 32 + C

Hope this helps!!
User Ezolotko
by
4.6k points
3 votes

Answer:

f=c+32

Explanation:

Eliminar paréntesis.

c=f-32

c=f−32

2 Suma 3232 a ambos lados.

c+32=f

c+32=f

3 Intercambia los lados.

f=c+32

f=c+32

User Jeena Rita
by
5.9k points